Liver Cirrhosis - Debates and Current Challenges 2019
DOI: 10.5772/intechopen.83481
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Cellular Aspects of Cirrhosis and How an Adenosine Derivative Could Revert Fibrosis

Abstract: Hepatic fibrosis occurs in response to persistent liver damage and is characterized by an excessive accumulation of extracellular matrix. When the damage is prolonged, there is a chronic inflammation and persistent hepatic fibrosis eventually leads to cirrhosis, where in addition to the scar, there is an important vascular remodeling associated with portal hypertension and, if decompensated, leads to death or can develop hepatocellular carcinoma. We have been studying the pharmacologic functions of adenosine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 102 publications
(113 reference statements)
0
3
0
Order By: Relevance
“…In Germany, more than 62,000 patients with chronic liver diseases were admitted to hospital in 2016 [ 5 ] showing an increasing trend and imposing a high medical and economic burden. Liver cirrhosis is the late and irreversible stage of hepatic fibrosis [ 6 ], pathologically representing a hepatic tissue remodeling with the formation of fibrotic interconnected septa that distort the liver tissue, divide the parenchyma in nodules and alter vascular architecture and resistance resulting in altered blood flow and portal hypertension [ 7 ]. The most common underlying etiologies of liver cirrhosis are alcohol abuse, chronic hepatitis B virus (HBV) and hepatitis C virus (HCV) infections, as well as non-alcoholic steatohepatitis (NASH) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Germany, more than 62,000 patients with chronic liver diseases were admitted to hospital in 2016 [ 5 ] showing an increasing trend and imposing a high medical and economic burden. Liver cirrhosis is the late and irreversible stage of hepatic fibrosis [ 6 ], pathologically representing a hepatic tissue remodeling with the formation of fibrotic interconnected septa that distort the liver tissue, divide the parenchyma in nodules and alter vascular architecture and resistance resulting in altered blood flow and portal hypertension [ 7 ]. The most common underlying etiologies of liver cirrhosis are alcohol abuse, chronic hepatitis B virus (HBV) and hepatitis C virus (HCV) infections, as well as non-alcoholic steatohepatitis (NASH) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This group reported that IFC-305 reduced cell survival in HCC cell lines but did not impair survival of a human hepatic progenitor cell line. (34)…”
Section: Hccmentioning
confidence: 99%
“…An adenosine derivative, IFC-305 (UNAM Patent 207422), administered in a cirrhotic rat model has previously been able to recover SAM levels abrogated in cirrhosis which triggers the re-establishment of 5mC and 5hmC in this condition . IFC-305 also has several hepatoprotective properties (reviewed in [Rodríguez-Aguilera et al, 2019]), such as, reduction of fibrosis and amelioration of liver function through regulation of transcriptome , promotion of cell cycle recovery in the liver [Chagoya de Sanchez et al, 2012], antiinflammatory effects during cirrhosis , prevention of hepatic stellate cells (HSCs) activation , and anti-carcinogenic effects [Velasco-Loyden et al, 2017].…”
Section: Introductionmentioning
confidence: 99%